Mitochondrial Ribosomal Protein L12 selectively associates with human mitochondrial RNA polymerase to activate transcription - Surovtseva, Yulia V. (National Academy of Sciences, 2011)
Basal transcription of human mitochondrial DNA (mtDNA) in vitro requires the single-subunit, bacteriophage-related RNA polymerase, POLRMT, and transcription factor h-mtTFB2. This two-component system is activated differentially at mtDNA promoters by human mitochondrial transcription factor A (h-mtTFA). Mitochondrial ribosomal protein L7/L12 (MRPL12) binds directly to POLRMT, but whether it does so in the context of the ribosome or as a “free” protein in the matrix is unknown. Furthermore, existing evidence that MRPL12 activates mitochondrial transcription derives from overexpression studies in cultured cells and transcription experiments using crude mitochondrial lysates, precluding direct effects of MRPL12 on transcription to be assigned. Here, we report that depletion of MRPL12 from HeLa cells by shRNA results in decreased steady-state levels of mitochondrial transcripts, which are not accounted for by changes in RNA stability. We also show that a significant “free” pool of MRPL12 exists in human mitochondria not associated with ribosomes. “Free” MRPL12 binds selectively to POLRMT in vivo in a complex distinct from those containing h-mtTFB2. Finally, using a fully recombinant mitochondrial transcription system, we demonstrate that MRPL12 stimulates promoter-dependent and promoter-independent transcription directly in vitro. Based on these results, we propose that, when not associated with ribosomes, MRPL12 has a second function in transcription, perhaps acting to facilitate the transition from initiation to elongation. We speculate that this is one mechanism to coordinate mitochondrial ribosome biogenesis and transcription in human mitochondria, where transcription of rRNAs from the mtDNA presumably needs to be adjusted in accordance with the rate of import and assembly of the nucleus-encoded MRPs into ribosomes.